Modernização e desburocratização do Comércio Internacional no Brasil: reformas políticas e ajustes normativos necessários à plena implementação do Acordo sobre a Facilitação do Comércio da OMC - Kotzias, Fernanda Vieira (2018)
The Trade Facilitation Agreement (TFA) represents an important step for Members of the World Trade Organization (WTO) towards the reduction of bureaucracy and transactional costs, as well to the increase in the transparency of foreign trade operations, in particular where Customs are concerned. The inclusion of this topic in WTO negotiations’ agenda was due to the perception that, as trade has become more liberalized, a new international regulatory architecture emerged, shifting the focus of policymakers from tariff barriers to other impediments to the cross-border movement of goods, particularly to those of an administrative and logistical nature. After almost twenty years of negotiations on its structure and content, the TFA was signed in 2013 during the Bali Conference and became effective in February 2017. Even though Brazil has only ratified the agreement in 2018 by means of Decree n. 9.326/2018, the Brazilian Government submitted its notification to WTO in 2016 designating 95.8% of the TFA commitments to be implemented immediately. The remaining 4.2% were scheduled to be implemented until December 2019. This was a bold position and has generated great expectations for operators and other interested parties in international trade. Nevertheless, Brazil remains poorly evaluated by national and international indicators that measure transaction costs, as most of the measures under the TFA continue to be totally or partially disregarded in practice, which is a major complain from the Brazilian private sector. In this context, the research problem addressed in this thesis is to identify the bottlenecks to the greater efficiency of the management of foreign trade in Brazil and evaluate the necessity of political, institutional and normative reforms and adjustments in order to foster the effective implementation of WTO trade facilitation obligations and increase Brazil’s integration into international trade. The proposed analysis is based on extensive bibliographical and documentary research, exploring doctrinal sources, national jurisprudence and WTO precedents to discuss the implications of the commitments signed within the scope of the WTO in the Brazilian legal system. From this, an attempt was made to inductively analyze the barriers to trade facilitation and legal uncertainty faced by trade operators. Finally, the research problem is addressed based on the study of foreign models and recommendations of international organizations. This thesis was structured in four chapters, in order to first present important concepts and delimitations in terms of trade facilitation and the way in which international obligations are internalized into the national legal order and discuss the Brazilian political-institutional structure regarding the regulation of foreign trade matters. Finally, based on the understandings and clarifications presented, recommendations are proposed for the implementation of trade facilitation in Brazil. Additionally, possible actions and reforms are directed to each of the main powers and articulators of Brazilian foreign trade individually, which are the Legislative Branch, the Executive Branch, the Judiciary Branch and the private sector